La littérature japonaise au xixe siècle. Deux ou trois récits d’une autre modernité - Emmanuel Lozerand (Itinéraires)
Did Japanese literature modernize under Occidental influence at the end of the nineteenth century? Or are there other narratives of Japan’s modernization, which would not rely on the theory of the “sleep of the East?” One can undoubtedly locate in the middle of the eighteenth century some evolutions that make it possible to describe Japanese modernity as indigenous but nevertheless similar to Western modernity. Does this mean, then, that Japan’s history and Occidental history converge? Certainly not.